(untitled) (Costos y Gestión, 2023)
Multifunctional health institutions play an indispensable role in the healthcare system, so it is necessary to ensure that the care provided to patients is of quality and supported by efficient and replicable processes. Information systems in these organizations still fail to timely meet the growing data needs for decision making. Regarding cost studies, there is no widespread agreement on the methodologies to be used or in determining the cost object. This paper proposes a model for the study, calculation, and projection of institutional costs at Clinica Universitaria Reina Fabiola. It establishes that the cost of the surgical hour in the period of May 2022 is 20.049,22, using as a basis the processes carried out, accounting and management information, and the support services involved in the organization of the Surgical Room Unit. The developed model aims to become a tool for decision-making by generating reliable cost statistics and projections under different assumptions. Regarding the environment, it provides useful information to compare market values and establish minimum values for negotiation with funders.